Two new species of Australopericoma Vaillant (Diptera: Psychodidae: Psychodinae) from the Brazilian Atlantic Rainforest - Araújo, Maíra Xavier; Bravo, Freddy (Zootaxa, 2020)
Two new moth fly species, Australopericoma onofrei sp. nov. and Australopericoma xavierae sp. nov., are described from the Atlantic Rainforest in the state of Bahia, Brazil. A new record of Australopericoma dissimilis Bravo from the state of Sergipe, Brazil and an updated species list are also provided.